Macro and Micro Determinants of Stock Return Companies in LQ-45 Index - Rahmat Fajar Basarda; Moeljadi Moeljadi; Nur Khusniyah Indrawati (Jurnal Keuangan dan Perbankan, 2018)
The purpose of this study is to analyze the influence of solvability ratio, market ratio, inflation and interest rate on stock return of company LQ-45 listed in Indonesia Stock Exchange. The population of this study is the companies included in the LQ-45 index in the listing on the Indonesia Stock Exchange during the period 2015-2016 amounted to 90 companies. Data analysis in this research used multiple regression. The results showed that the variable solvabilities proxied with debt to equity ratio have a negative and significant effect on stock returns. The market ratio variable is proxied by price to book value have the positive and significant effect on stock return. The market ratio variable is proxied by price earnings ratio has the positive and significant effect on stock return. This means that any increase in the percentage of market value proxied by price earnings ratio will increase stock return. Inflation variable has a negative and significant effect on stock return. This means any increase in inflation will reduce the stock return, and interest rate variables have a positive and significant effect on stock returns.JEL Classification: D04; E44; G11DOI: https://doi.org/10.26905/jkdp.v22i2.1439